Entitlements, Capabilities, and Crisis in the United Kingdom. (March 2020) - Hartworth, Christopher; Richards, Carol; Convery, Ian
This paper examines whether Amartya Sen's entitlements and capabilities concepts can be transferred in their application from low-income countries to high-income countries, specifically Cumbria, Northern England. Originally used to understand the causes of famine, these concepts have previously been used in several different geographical contexts to broadly understand poverty and inequality but almost entirely in low-income countries. This paper applies these concepts to a United Kingdom context in an attempt to understand the causes of poverty and inequality among people experiencing "livelihood crisis." The research uses data from two nongovernmental social welfare projects to examine the causes of crisis and the remedial effects of the intervention. Our findings indicate that these concepts can help to explain how people find themselves in crisis in Cumbria. On a broader level, they can also be used to explain poverty, inequality, and disadvantage in communities in the United Kingdom. The authors put forward that entitlements and capabilities provide a useful framework to advance the policy and political debate on the causes of poverty by providing a straightforward language and broad application. Entitlement and capabilities can also assist social welfare programs in framing their aims and objectives and through improved understanding about the causes of inequality, will be better able to support people out of disadvantage by strengthening entitlements and building capabilities, without the necessity of large-scale investment.